Fisioterapia Aquática na Transferência do Sentado para Ortostatismo no Paciente com AVC: Relato de Caso - Lima, Paula Nascimento [UNESP]; de Souza, Camila Mottineli; Andrade, Sonia da Silva; Cyrillo, Fábio Navarro; Braga, Douglas Martins (Universidade Federal de Sao Paulo, 2013)
Introduction. Studies show that 70% of body weight in patients with stroke during the transfer from sitting to standing position is transferred to the uninvolved limb. Significantly interfering with activities of daily living. Objective. The influence of aquatic therapy on eight in the affected hemisphere during the transition from sitting to standing. Method. Participated in this study a patient with right hemiparesis, the protocol lasted eight sessions in a liquid medium. The data of activation of the gluteus muscle were collected from surface electromyography and data as the weight transfer was examined by baropodometry platform. Results. Initial electromyography (151.1uv right gluteus maximus and left gluteus maximus 229.1uv) and Final electromyography (113.6 uv right gluteus maximus and left gluteus maximus113.3uv). Evolution was 19% in weight transferin paretic hemibody compared the pre and post intervention. Conclusion. The results showed that treatment was favorable to the patient, because at the end of application of the observed activation of the gluteus maximus and improved weight-bearing, and consequently these factors interfered positively in the security and independe in transferring from sitting to standing position.
Aquatic physical therapy at the sit to stand transfer in stroke: A case study
Keywords: Hidrotherapy; Paresis; Stroke; body position; case report; cerebrovascular accident; clinical trial; electromyography; gluteus maximus muscle; hemiparesis; human; human tissue; hydrotherapy; physiotherapy; sitting; standing; weight bearing